Long-term trends in life expectancy and active life expectancy in the United States - Manton, K. G.; Gu, X.; Lamb, V. L.
gráfs.
pp. 81-105
Keywords: Esperanza de Vida; Estados Unidos de America; Politica Sanitaria; Seguridad Social; Servicios de Salud